An Exploratory Study on The Presentation of Separate Financial Statements By Listed European Union Entities - Marek WIERZBIŃSKI; Zofia WIERZBIŃSKA (Communications of International Proceedings, 2024)
The International Accounting Standard (IAS) 27 should be used in the presentation of separate financial statements (SFS) for entities listed on regulated markets within the European Union (EU) that adopt the standards issued by the International Accounting Standards Board (IASB) as adopted by EU (hereinafter simply referred as IAS). This exploratory study aims to assess the entities in the listed EU indices that presented SFS under IAS. The study sample consists of entities from the major indices of EU countries for which the use of IAS in SFS is required or permitted, and it used a quantitative methodology, resorting to the method of documentary research. The findings show that most entities presented SFS, regardless of whether they were required or permitted, which is also consistent across countries. These results may indicate that the entities consider SFS relevant to provide information to stakeholders. Despite being a topic of increasing interest, a significant gap regarding the matters related to SFS remains in the literature. Consequently, this study, although exploratory, contributes to literature on the presentation of SFS by listed entities in Europe.
Keywords: IAS 27; separate financial statements; IFRS; financial investments